(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
This paper delves into the profound significance of nature in the works of prominent Romantic poets, including William Wordsworth, Samuel Taylor Coleridge, Percy Bysshe Shelley, and John Keats. It argues that nature transcends mere backdrop to become a primary character, shaping poetic themes, influencing language, and offering a canvas for exploring philosophical inquiries, spiritual connections, and emotional expression. Analysing key poems through the lens of pantheism, the role of imagination, and the symbolic potential of landscape, the paper illuminates how Romantic poets utilize nature to challenge societal norms, express personal anxieties and aspirations, and ultimately, reveal a nuanced understanding of the human condition in relation to the natural world.